Review on landfill gas formation from leachate biodegradation / Nur Shuhadah Japperi …[et al.] - Japperi, Nur Shuhadah; Mohd Asri, Zharif Zainulazfar; Wan Bakar, Wan Zairani; Dollah, 'Aqilah; Ahmad Fuad, Mohd Fazril Irfan; Che Mohamed Hussein, Siti Nurliyana (Universiti Teknologi MARA, 2021)
Landfill waste management is a very crucial procedure in handling Municipal Solid Waste (MSW) because it may create significant environmental issues if it is not managed properly. Landfill leachate and landfill gas (LFG) is part of the landfill waste management which triggered lot of researchers especially in terms of the environmental implications associated with the movement of the gasses during the waste constituents’ processes. Hence, this paper review is aiming to understand the behaviour of leachate itself as a decomposition agent in producing landfill gas (biogas). Biogas is naturally produced by anaerobic bacteria through anaerobic digestion which is affected by operating parameters and substrate characteristic. The results indicate that temperature, pH, and C/N ratio of leachate are the important factors that could increase the production of biogas with high content of methane. Furthermore, in terms of microbial activity during anaerobic digestion process, hydrogenotrophic and acetoclastic methanogen are the dominant substrate that contribute in producing methane gas as the final product. Firmicutes and Bacteroidetes are the common fermentative bacteria that had been found during fermentation process in hydrolysis and acidogenic phases. While, methanobacterial, methanococcal, methanomicrobial, methanosarcinal, and methanopyral are being classified as orders among 65 types of methanogenic archaea during methanogenesis stage. Overall, the relationships between operating parameters and microbial structure are important aspects that need to be considered in order to optimize the production of methane gas.